7 - Relations de genre et relations conjugales: by Jeanne Nanitelamio - Jeanne Nanitelamio (Africa Development, 1995)
This psychological survey on the gender and marital relations among the Kongos - a matrilinear ethnic group - was carried out through some sixty semi-structured interviews. The results highlight the dynamic changes in the husband and wife relation, in the emergency systems and in the women's roles and power relations.